2019
DOI: 10.1002/lipd.12150
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Rapid Assessment Questionnaire Using a Biomarker for Dietary Intake of n‐3 Fatty Acids

Abstract: While there is considerable evidence supporting health benefits of consuming diets high in omega-3 (n-3) fatty acids, there is no quick and effective tool to measure n-3 intake. The objective of this study was to evaluate the accuracy of a rapid assessment questionnaire (the Omega-3 Checklist) used to quantify intake of n-3 fatty acids. This was done by comparing n-3 intakes to blood biomarkers of n-3 exposure in a population of healthy men and women. In addition, a separate analysis was run including covariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Some studies have demonstrated that BMI and gender may alter blood levels of polyunsaturated fatty acids. [ 44,45 ] When BMI or gender were tested for affecting the cumulative levels of LA in PBMCs, erythrocytes or plasma, and LA 4 CL, neither variables modified the effect of diet group on changes of LA or LA 4 CL.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have demonstrated that BMI and gender may alter blood levels of polyunsaturated fatty acids. [ 44,45 ] When BMI or gender were tested for affecting the cumulative levels of LA in PBMCs, erythrocytes or plasma, and LA 4 CL, neither variables modified the effect of diet group on changes of LA or LA 4 CL.…”
Section: Resultsmentioning
confidence: 99%
“…[ 77 ] A partial description of the study design, participant inclusion and exclusion criteria, and methods was described previously. [ 44 ] Written informed consent was provided by all participants. Healthy adults (≥18 years old) were recruited from the Columbus, Ohio area.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to low recruitment, study criteria were revised to include men and women aged 18 to 50 years, body mass index between 18 and 34.9 kg/m 2 , and free of major medical conditions. Exclusion criteria included: smoking and nicotine use, steroid use other than oral contraceptives for women, pregnancy or lactation, diagnosed eating disorder, diabetes, diagnosed cardiovascular, pulmonary, skeletal, and metabolic diseases, use of medications known to affect appetite, blood lipids, body composition, body weight, or food intake (appetite control drugs, steroids, or antidepressants), women not using oral hormonal contraception, and high LCn-3 intake measured by the “Omega-3 checklist” [ 26 ]. Participants were excluded if they had lost > 10% of their weight in the two months preceding screening and/or were actively attempting weight loss.…”
Section: Methodsmentioning
confidence: 99%